2017
DOI: 10.1186/s13613-017-0302-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of argatroban in patients with acute respiratory distress syndrome and extracorporeal lung support

Abstract: BackgroundExtracorporeal membrane oxygenation (ECMO) or pumpless extracorporeal lung assist (pECLA) requires effective anticoagulation. Knowledge on the use of argatroban in patients with acute respiratory distress syndrome (ARDS) undergoing ECMO or pECLA is limited. Therefore, this study assessed the feasibility, efficacy and safety of argatroban in critically ill ARDS patients undergoing extracorporeal lung support.MethodsThis retrospective analysis included ARDS patients on extracorporeal lung support who r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 31 publications
5
77
0
1
Order By: Relevance
“…The single center study supported that patients anticoagulated with argatroban had no difference in major or minor bleeding and had more goal aPTT values compared to UFH controls [43]. Multiple studies have shown that doses vary widely between adult and pediatric patients anticoagulated with argatroban on ECMO, thus careful monitoring is imperative to ensure optimal anticoagulation [43][44][45]. A literature analysis reviewed nine articles describing 34 patients anticoagulated with argatroban.…”
Section: Argatrobanmentioning
confidence: 91%
“…The single center study supported that patients anticoagulated with argatroban had no difference in major or minor bleeding and had more goal aPTT values compared to UFH controls [43]. Multiple studies have shown that doses vary widely between adult and pediatric patients anticoagulated with argatroban on ECMO, thus careful monitoring is imperative to ensure optimal anticoagulation [43][44][45]. A literature analysis reviewed nine articles describing 34 patients anticoagulated with argatroban.…”
Section: Argatrobanmentioning
confidence: 91%
“…Experience and data regarding the use of DTIs for anticoagulation in ECMO patients is essentially limited to cases of HIT (35)(36)(37). Only a few studies have compared DTIs anticoagulation to standard UFH anticoagulation (38,39).…”
Section: Alternatives To Ufh: Argatroban and Bivalirudin Anticoagulatmentioning
confidence: 99%
“…Die Inzidenz an Blutungen und thrombembolischen Komplikationen unterschied sich nicht zwischen den verschiedenen Antikoagulanzien. Eine interessante Beobachtung war, dass die Patienten unter Argatroban das aPTT-Ziel schneller erreichten und als Ausdruck der besseren Steuerbarkeit stabiler im Zielkorridor waren [29].…”
Section: Klinischer Einsatz Und Datenlageunclassified